Estimating the Relationship between Price and Time to Sale for Investment Property - Trippi, Robert R. (Management Science, 1977)
This article develops an empirical model for estimating the relationship between selling price and length of time on market for a unique, large-ticket item. The model provides valuable information in the form of probability statements concerning the length of time to sale at any given price for a capital asset having a well-defined set of characteristics.